2019
DOI: 10.4103/aer.aer_36_19
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of symphysiofundal height and abdominal girth with the incidence of hypotension in cesarean section under spinal anesthesia using bupivacaine with fentanyl as adjuvant: A clinical study

Abstract: Background and Aims: A decreased lumbosacral subarachnoid space volume is a major factor in cephalad intrathecal spread of local anesthetic in term parturients due to compressive effect of the gravid uterus. The aim of this study was to assess the relationship of symphysiofundal height (SFH) and abdominal girth (AG) with the incidence of hypotension and the highest level of sensory blockade. Settings and Design: This study was a prospective observational study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Maternal factors such as weight, BMI, [14][15][16] weight gain during pregnancy, 20 abdominal girth, and distance between the symphysis pubis and fundus 21 have been reported to be able to predict SAIH due to aortocaval compression. 16,[22][23][24] However, fetal weight, which was identified as a risk factor for SAIH in this study, may represent this compression more directly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal factors such as weight, BMI, [14][15][16] weight gain during pregnancy, 20 abdominal girth, and distance between the symphysis pubis and fundus 21 have been reported to be able to predict SAIH due to aortocaval compression. 16,[22][23][24] However, fetal weight, which was identified as a risk factor for SAIH in this study, may represent this compression more directly.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the parturients without SAIH, those with SAIH had a significantly lower baseline SBP (122 [interquartile range = 114-130] vs 130 [120-143] mmHg, p < 0.001), heavier large fetal weight (3098 [2742-3345] vs 2930 [2576-3266] g, p < 0.001), were more often multiparous (259 [60.4%] vs 261 [45.8%], p < 0.001), had a higher percent change in lowest SBP (33 [27-39] vs 19 [12][13][14][15][16][17][18][19][20][21][22][23][24][25]%, p < 0.001), and shorter time to lowest SBP after spinal anesthesia (14.9 [10][11][12][13][14][15][16][17][18][19][20] vs 15.9 [10][11][12][13][14][15][16][17][18][19][20] minutes, p < 0.001).…”
Section: Univariate Analysis Of Saihmentioning
confidence: 99%
“…Fakherpour et al 31 found that gravidity ≥4 and history of hypotension were associated with spinal anesthesia-induced hypotension. Parthasarathy et al 32 found that the distance between the symphysis pubis and the fundus and abdominal girth could effectively predict spinal anesthesia-induced hypotension, however, this correlation was not confirmed by Kuok et al 33 and Günüşen et al 34…”
Section: Domain I Demographic Characteristicsmentioning
confidence: 96%